Hydrochar and hydrochar co-compost from OFMSW digestate for soil application: 2. agro-environmental properties. (15th June 2022) - Bona, Daniela; Scrinzi, Donato; Tonon, Giustino; Ventura, Maurizio; Nardin, Tiziana; Zottele, Fabio; Andreis, Daniele; Andreottola, Gianni; Fiori, Luca; Silvestri, Silvia
Abstract: The work concerns the study of the hydrochar from digestate and hydrochar co-compost characterization as amendments. The processes for hydrochar and co-compost production were described in Part 1 of this work (Scrinzi et al., 2022). The amendment properties of hydrochar (produced at 180–200–220 °C for 3 h) and co-composts (25%, 50%, and 75% hydrochar percentage of digestate substitution) were assessed by phytotoxicity, plant growth bioassay, and soil effect. Different seeds species ( Lepidium sativum, Cucumis sativus, and Sorghum bicolor sp.) were dosed at increased concentrations using both wet raw amendments and their water extracts. The chemical characterization showed phytotoxic compounds content depending on both the initial feedstock (digestate) and the HTC process; at the same time, the analysis highlighted the reduction of these compounds by composting (organic acid, polyphenols, salt concentration). The dose-response was analyzed by the Cedergreen-Streibig-Ritz model and the half-maximal effective concentration (EC50) was calculated based on this equation. The soil properties and GHG emissions measurements (CH4, CO2, N2 O, and NH3 ) highlighted the effect on N dynamics and on soil respiration induced by substrates. The HC200 soil application determined a significant impact on CO2 and N2 O emission and NH3 volatilization (10.82 mol CO2 /m 2 ; 51.45 mmol N2 O/m 2 ; 112 mol NH3 /m 2 ) and a significant reduction of total N and TOC (46% of TKN and 49% of TOC). The co-compost (75%) showed specific effects after soil application compared to other samples an increase of available P (48%), a greater content of nitrogen (1626 mg/kg dry basis), and a reduction of organic carbon (17%). Our results demonstrate the good quality of co-compost and at the same time the validity of this post-treatment for addressing many issues related to hydrochar use in the soil as an amendment, confirming the suitability of HTC process integration for digestate treatment in anaerobic digestion plants. Graphical abstract: Image 1 Highlights: Amendment properties of hydrochar and co-composts are assessed. Hydrochar from OFMSW digestate shows a hormetic effect in germination tests. Co-compost shows a phytostimulation effect on seeds germination. Hydrochar has an impact on NH3, CO2, CH4, and N2 O emissions. Co-compost determines a specific effect on P, N, and C soil content.